Characterization and monitoring of the regolith aquifer within four selected cascades (sub-watersheds) of the Malala Oya Basin [Sri Lanka]. - Panabokke, Christopher R.; Ariyaratne, Badugodahewa Ranjith; Seneviratne, A.; Wijekoon, D.; Molle, Francois (International Water Management Institute, 2007)
The groundwater present in the hard rock region of the dry zone of Sri Lanka is made up of the shallow 'Regolith Aquifer' and the deeper fracture zone aquifer is now clearly recognized. However, up to now no study had been carried out or reported in this country on the dynamic nature of this shallow regolith aquifer. This is the very first study carried out and reported in this regard. As part of the study, the impact of the Mau Ara trans-basin canal on the groundwater conditions below the area of influence of this trans-basin feeder canal has also been examined.